2006
DOI: 10.1590/s1415-43662006000100005
|View full text |Cite
|
Sign up to set email alerts
|

Variabilidade espacial de classes de textura, salinidade e condutividade hidráulica de solos em planície aluvial

Abstract: Visando-se avaliar a distribuição de classes texturais e sua correlação espacial com a infiltrabilidade e salinidade de uma área aluvial, no Agreste de Pernambuco, utilizou-se a geoestatística indicadora segundo uma distribuição binária baseada na presença/ausência de solos francos. Considerando-se pontos de amostragem e de testes de infiltração dispostos ao longo do eixo principal do aluvião, e aleatoriamente distribuídos, analisou-se a variabilidade espacial das classes de solo predominantes, da velocidade d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
50

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 21 publications
(24 reference statements)
2
27
0
50
Order By: Relevance
“…The same result was found by Montenegro & Montenegro (2006) studying the spatial patterns of soil EC on an alluvial plain of the Pernambuco semi-arid region. Gomes & Fizziola (2006) pointed out that, in arid and semi-arid regions, EC values above 4.00 dS m -1 can cause severe limitations to crop development.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The same result was found by Montenegro & Montenegro (2006) studying the spatial patterns of soil EC on an alluvial plain of the Pernambuco semi-arid region. Gomes & Fizziola (2006) pointed out that, in arid and semi-arid regions, EC values above 4.00 dS m -1 can cause severe limitations to crop development.…”
Section: Resultssupporting
confidence: 82%
“…Montenegro & Montenegro (2006) conducted a study on the spatial variability of soil textural classes, salinity and electrical conductivity on an alluvial plain of the Pernambuco semi-arid region, and found that geostatistics represented well the spatial correlation between the studied attributes.…”
Section: Introductionmentioning
confidence: 99%
“…The predominant vegetation is hyperxerophilic Caatinga (Montenegro & Montenegro, 2006), an exclusively Brazilian biome.…”
Section: Methodsmentioning
confidence: 99%
“…The annual mean rainfall is 607 mm, mean temperature of 23 ºC and the potential evapotranspiration is about 2,000 mm per year. The dominant vegetation is hypoxerophilous caatinga (Montenegro & Montenegro, 2006).…”
Section: Characterization Of the Study Areamentioning
confidence: 99%